Conquer The Chaos : How to Grow a Successful Small Business Without Going Crazy - Mask, Clate and Martineau, Scott (Hoboken Wiley, 2010)
Create the business you want without sacrificing the lifestyle you deserve. The majority of new entrepreneurs (and even those with a little more experience) are finding themselves trapped, controlled, and consumed by their own businesses. They are struggling just to keep their businesses running, let alone actually growing their companies and experiencing the success they anticipated. Conquer the Chaos speaks to you as a small business owner by making sense of the overwhelming demands on your business and providing a twenty-first century recipe for success with sanity. With engaging stories, q.
Include Index, Appendix and Illustration
Keywords: Small business--Growth -- Small business--Management -- Strategic planning